Case report: A case of primary cardiac malignant mesothelioma - Wang, Ao; Liu, Baohui; Dong, Shengjun; Wang, Yujiu (Frontiers in Oncology, 2024)
Primary cardiac malignant tumors are extremely rare, making up about 10% of all primary cardiac tumors. Most of these tumors are primary sarcomas, with primary mesothelioma being even less common. This report details a 53-year-old male patient diagnosed with primary cardiac malignant mesothelioma. The patient had symptoms of chest pain and difficulty breathing. A CT scan showed an enlarged heart, fluid around the heart, and irregular thickening of the pericardium. Diagnosis was confirmed through a surgical biopsy, which showed the presence of malignant mesothelioma. After the procedure, the patient received appropriate cardiac support. Although stable at discharge, the patient unfortunately died three months later due to severe wheezing.There may be a potential link between exposure to radioactive iodine treatment and this outcome. This case highlights the diagnostic and treatment challenges of primary cardiac malignant tumors and reminds physicians to consider this rare disease when evaluating patients with similar symptoms.